2018
DOI: 10.1007/s00787-018-1124-1
|View full text |Cite
|
Sign up to set email alerts
|

An international clinical study of ability and disability in ADHD using the WHO-ICF framework

Abstract: This is the fourth and final study designed to develop International Classification of Functioning, Disability and Health (ICF, and children and youth version, ICF-CY) core sets for attention-deficit hyperactivity disorder (ADHD). To investigate aspects of functioning and environment of individuals with ADHD as documented by the ICF-CY in clinical practice settings. An international cross-sectional multi-centre study was applied, involving nine units from eight countries: Denmark, Germany, India, Italy, Portug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 60 publications
1
22
0
2
Order By: Relevance
“…The scoping review identified 50 [36], the international expert survey 53 [37], the qualitative study 82 [38], and the clinical cross-sectional study 109 second-level candidate categories [39]. Taken together, the four preparatory studies identified 132 unique second-level ICF candidate categories.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The scoping review identified 50 [36], the international expert survey 53 [37], the qualitative study 82 [38], and the clinical cross-sectional study 109 second-level candidate categories [39]. Taken together, the four preparatory studies identified 132 unique second-level ICF candidate categories.…”
Section: Resultsmentioning
confidence: 99%
“…The aim of the international consensus conference described in this paper was to develop Comprehensive and Brief ICF Core Sets for ADHD based on the evidence collected through four international preparatory studies, i.e., a scoping review [36], an expert survey [37], a qualitative study [38], and a clinical cross-sectional study [39]. This aim was fulfilled by an international multiprofessional group of experts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…En la actualidad se están desarrollando estudios transculturales para diseñar el conjunto básico de la Clasificación Internacional del Funcionamiento, la Discapacidad y la Salud (CIF) para el TDAH, dado que se reconocen muchas categorías, en su mayoría desde las funciones corporales, las actividades personales, la participación social y los factores ambientales (9,10).…”
Section: Introductionunclassified